Growth evaluation of all male prawn and tilapia in ponds of northern Bangladesh - Rahman, SH; Hossain, Md Akhtar; Hossain, Md Rayhan; Sultana, Sayeeda (Asian Journal of Medical and Biological Research, 2017)
Freshwater aquaculture is by far the most ancient aquatic living resource production system known in the world. An experiment was conducted to evaluate the growth performance of prawn and tilapia (male) under different sex (male and female) contribution of prawn in polyculture ponds for a period of four months from September 2010 to December 2010. The experiment was designed with 3 treatments like T1 (All male Tilapia 4938/ha + All male Prawn 19,753/ha), T2 (All male Tilapia 4938 / ha + All female Prawn 19,753/ha) and T3 (All male Tilapia 4938/ decimal + all male Prawn 19876 + all female prawn 19876/ha), each with 2 replications. The mean stocking weight of prawn was 2.87 g and that of tilapia was 37.36 g. Total stocking density of prawn and tilapia (24,691/ha), basal fertilization (Cowdung 2470kg/ha, Urea 50kg/ha and TSP 50kg/ha), periodic fertilization (Cowdung 50kg/ha/day, urea 1.25kg/ha/day and TSP 1.25kg/ha/day) and feeding regime (diet containing 30% protein level at the rate of 2-5% of prawn and fish body weight twice daily) were same for all the treatments. Water quality parameters (water temperature, transparency, dissolved oxygen, pH, NH3-N and alkalinity) were monitored fortnightly and the growth parameters were monitored monthly. Mean values of water quality parameters were found within the suitable range. Treatment T1 varied more significantly (P<0.05) than that of others for the mean values of growth parameters (final weight, weight gain, SGR, survival rate and yield) of prawn and tilapia. Asian J. Med. Biol. Res. June 2017, 3(2): 198-204